The Educational Model in Mexico: A Review of its Scope and a Perspective for the Future - Azamar Alonso, Aleida (Rastros Rostros, 2015)
Purpose: the educational model in Mexico responds to an agenda that do not match social reality, since overcoming poverty and marginalization is not guaranteed with this model. This article analyzes the historical formation of the educational process in Mexico, from the eighties until 2010. Description: this research of explanatory nature aims to understand the evolution of the educational structure in Mexico and verify if its development is consistent with the economic objective included in the national development model. For this reason, data collection is both qualitative and quantitative. Data were obtained from the National Statistical Education Information System and through official publications. Point of view: the proposals of the unschooling movement are discussed in order to develop a critical perspective to determine whether the educational model now applied responds to the major social interests or whether, by contrast, it requires a reform based on the ideas proposed by authors like Ilich, McLuhan or Freire, according to which individuals and society are responsible for the educational process through non-centralized or technically/economically oriented bodies or networks. Conclusions: an educational model unable to respond to demand, behind the times, and with zero profit regarding new social paradigms is observed; therefore, it is necessary to analyze in depth the objectives to be met